Kesulitan Siswa Dalam Menyelesaikan Soal-Soal PISA Tahun 2012 Level 4, 5, dan 6 di SMP N 1 Indralaya - Dewi, Agatha Indy Candra; Zulkardi; Hartono, Yusuf (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
The purpose of this research is to find student’s difficulties in resolving PISA 2012 problems level 4, 5, and 6. The method that used in this research is qualitative study. The type of this research is descriptive study that attempts to identify and describe the difficulties that experienced by student in resolving PISA 2012 problems level 4, 5, and 6. Five sixth grade students of SMP N 1 Indralaya become the research subject in this research. The results of this research shows that the students have difficulty in understanding the problems, modifying real problems into mathematics structure, and solving mathematics problem in resolving PISA 2012 problems level 4, 5, and 6. In resolving level 4 problem, students also have difficulty in interpreting mathematical solution in terms of real situation. However, there is a student who capable to resolve the problems level 4, 5, and 6 correctly.